2017
DOI: 10.3390/su9122303
|View full text |Cite
|
Sign up to set email alerts
|

The Role Played by Trust and Its Effect on the Competiveness of Logistics Service Providers in Hungary

Abstract: This research focuses on the role of trust and the impact of its level on the revenue, earnings before tax and the degree of flexibility of logistics service providers (LSPs). More specifically, the role of the executive manager is examined in relation to the impact of business relationships (trust levels) within and between organizations. In addition, the analysis covers the development of revenue, earnings before tax and degree of flexibility of logistics service providers in the context of the role of the h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
31
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 33 publications
(32 citation statements)
references
References 90 publications
1
31
0
Order By: Relevance
“…This finding was in line with the insight that the marketing strategy should have emphasized on the niche that comprised of visionaries and technology enthusiasts as the early adopters of the new high-tech products [69,70]. Indonesian airlines were left behind in recognizing and addressing environmental concerns.…”
Section: Discussionsupporting
confidence: 62%
“…This finding was in line with the insight that the marketing strategy should have emphasized on the niche that comprised of visionaries and technology enthusiasts as the early adopters of the new high-tech products [69,70]. Indonesian airlines were left behind in recognizing and addressing environmental concerns.…”
Section: Discussionsupporting
confidence: 62%
“…Existing studies have confirmed links between trust and collaboration [32]. Oláh, Bai, Karmazin, Balogh, and Popp [93] argued that a higher level of trust implies better results and greater output. Numerous scholars have indicated an association between trust and high work engagement and job satisfaction in teams [57,94].…”
Section: Interpersonal Trust and Team Collaborationmentioning
confidence: 93%
“…These evidences also suggest it is worth monitoring the quality of governance across and within individual countries for better development over time. From another point of view, the existing financial challenges regarding, i.e., debt enforcement, risk management [41], organizational culture [42] and trust [43], etc. represent a respectable opportunity for further research in the case of accounting fraud analysis.…”
Section: Discussionmentioning
confidence: 99%